“It’s always been a challenge, right?” An analysis of the affordances and limitations of STEM educators’ attempts to improve gender equity in Global South and North makerspaces - Archer, Louise; Freedman, Esme; Nag Chowdhuri, Meghna; DeWitt, Jennifer; Liu, Qian; Garcia Gonzalez, Francisco (Frontiers in Education, 2025)
IntroductionThe longstanding, chronic under-representation of girls/ women and non-binary youth in engineering and computing remains a global concern. Informal STEM learning contexts, such as makerspaces, have the potential and flexibility to engage all young people with STEM in creative, engaging and equitable ways. Yet to date, this potential remains largely un-realized, with many makerspaces remaining ‘chilly’, male-dominated spaces (materially, spatially, relationally and socially). This paper seeks to contribute to understanding of the challenges and possibilities for more gender equitable practice in makerspaces.MethodsThe paper analyses multimodal data collected by academic and youth co-researchers over two years from two Global North and two Global South makerspaces, as part of a collaborative research-practice partnership project.ResultsThe paper considers educators’ attempts to evolve and improve gender equitable practice in their settings, shared challenges and barriers to gender equity, steps taken by practitioners to support greater gender equity within their settings (through access/outreach, governance/staffing and pedagogy) and the challenges and blocks they encountered to progress.DiscussionImplications are discussed for advancing equitable practice to support the participation of girls/ young women and non-binary youth within STEM and makerspaces.